2019
DOI: 10.1155/2019/3815786
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Prolongs Survival of the Orthotopic Hepatocellular Carcinoma Model by Inducing Apoptosis and Inhibiting Angiogenesis

Abstract: Aim. Microvessel density is a marker of tumor angiogenesis activity for development and metastasis. Our preliminary study showed that ginsenoside Rg3 (Rg3) induces apoptosis in hepatocellular carcinoma (HCC) in vitro. The aim of this study was to investigate the cross-link for apoptosis induction and antiangiogenesis effect of Rg3 on orthotopic HCC in vivo. Methods. The murine HCC cells Hep1-6 were implanted in the liver of mouse. With oral feeding of Rg3 (10 mg/kg once a day for 30 days), the quantitative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In vivo studies have revealed that direct targeted inhibition of VEGF by ginsenoside Rg3 in combination with TACE blocked angiogenesis and tumor growth, eventually reducing the tumor size and metastasis and prolonging OS in a buffalo rat orthotopic liver cancer model and rabbit liver VX2 carcinoma models ( Yu et al, 2013 ; Zhou et al, 2014 ). The inhibitory effect of ginsenoside Rg3 on tumor MVD was also observed in C57BL/6 mice implanted with Hepa1-6 cells, and ginsenoside Rg3 initiated apoptosis of the tumor cells ( Li et al, 2018 ), decreased the tumor volume and ability of the tumor to generate vascularized networks, and inhibited further growth and remote metastasis ( Hu et al, 2019 ). Ginsenoside Rg3 has shown good antitumor activity in vivo and is well tolerated without significant toxic side effects, but it has low water solubility and poor oral bioavailability, which affect clinical applications.…”
Section: Investigations On Chinese Herbal Medicine-derived Compounds ...mentioning
confidence: 90%
“…In vivo studies have revealed that direct targeted inhibition of VEGF by ginsenoside Rg3 in combination with TACE blocked angiogenesis and tumor growth, eventually reducing the tumor size and metastasis and prolonging OS in a buffalo rat orthotopic liver cancer model and rabbit liver VX2 carcinoma models ( Yu et al, 2013 ; Zhou et al, 2014 ). The inhibitory effect of ginsenoside Rg3 on tumor MVD was also observed in C57BL/6 mice implanted with Hepa1-6 cells, and ginsenoside Rg3 initiated apoptosis of the tumor cells ( Li et al, 2018 ), decreased the tumor volume and ability of the tumor to generate vascularized networks, and inhibited further growth and remote metastasis ( Hu et al, 2019 ). Ginsenoside Rg3 has shown good antitumor activity in vivo and is well tolerated without significant toxic side effects, but it has low water solubility and poor oral bioavailability, which affect clinical applications.…”
Section: Investigations On Chinese Herbal Medicine-derived Compounds ...mentioning
confidence: 90%
“…Moreover, ginsenoside Rg3 reduces phosphorylation of STAT3 resulting from hypoxic conditions, phosphorylation of ERK 1/2, JNK, and decreases VEGF expression [168]. Ginsenoside Rg3 was shown to inhibit microtumor vessel formation activation in mice when given at a dose of 10 mg/kg once a day and it contributed to tumor shrinkage and increased animal survival [169]. A study that assessed the pharmacokinetics of Ginsenoside Rg3 found that it was well tolerated by humans when administered intramuscularly at a dose ranging from 10-60 mg once every two days [170].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Ginsenoside Rg3 (Rg3) is a terpenoid and an active component of ginseng, which can affect multiple metabolic pathways and play a variety of roles in the body, such as repairing damage and anti-tumor and anti-oxidation effects [ 11–13 ]. Recently, several studies have confirmed that Rg3 effectively inhibits HCC progression [ 14 , 15 ]. However, the role of Rg3 and SFN combination therapy in HCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%